Activation of prostaglandin E2 EP1 receptor increases arteriolar tone and blood pressure in mice with type 2 diabetes. - Rutkai, I; Feher, A; Erdei, N; Henrion, D; Papp, Z; Edes, I; Koller, A; Kaley, G; Bagi, Z (2009)
AIMS: Type 2 diabetes mellitus is frequently associated with hypertension, but the underlying mechanisms are not completely understood. We tested the hypothesis that activation of type 1 prostaglandin E(2) (PGE(2)) receptor (EP1) increases skeletal muscle arteriolar tone and blood pressure in mice with type 2 diabetes. METHODS AND RESULTS: In 12-week-old, male db/db mice (with homozygote mutation in leptin receptor), systolic blood pressure was significantly elevated, compared with control heterozygotes. Isolated, pressurized gracilis muscle arterioles ( approximately 90 microm) of db/db mice exhibited an enhanced pressure- and angiotensin II (0.1-10 nM)-induced tone, which was reduced by the selective EP1 receptor antagonist, AH6809 (10 microM), to the level observed in arterioles of control mice. Exogenous application of PGE(2) (10 pM-100 nM) or the selective agonist of the EP1 receptor, 17-phenyl-trinor-PGE(2) (10 pM-100 nM), elicited arteriolar constrictions that were significantly enhanced in db/db mice (max: 31 +/- 4 and 29 +/- 5%), compared with controls (max: 20 +/- 2 and 14 +/- 3%, respectively). In the aorta of db/db mice, an increased protein expression of EP1, but not EP4, receptor was also detected by western immunoblotting. Moreover, we found that oral administration of the EP1 receptor antagonist, AH6809 (10 mg/kg/day, for 4 days), significantly reduced the systolic blood pressure in db/db, but not in control mice. CONCLUSION: Activation of EP1 receptors increases arteriolar tone, which could contribute to the development of hypertension in the db/db mice.